Exploring Elementary Teachers', Students' Beliefs and Readiness toward STEAM Education - Kartini, Dwi; Widodo, Ari (Universitas Pendidikan Indonesia, 2020)
21st century demands education to promote students with STEAM competencies. Most researches on STEAM are mainly focused on students’ learning outcomes on STEAM, but only few address non-cognitive aspects. It is necessary to examine elementary teachers and students’ beliefs and readiness towards STEAM learning. The purpose of this research is to explore teachers’ and students’ beliefs and readiness towards STEAM learning. The survey-designed method was used in this research. A total of 34 elementary school teachers and 36 elementary school students in the city of Bandung participated in this research. The samples were selected using a random sampling technique. Questionnaires were used to collect research data. The results obtained from this research show that students and teachers have positive perceptions in career and benefit of STEAM learning. Students are actually interested in STEAM learning, but the competencies and factors that support and stimulate STEAM learning in schools are still low. The teacher has low competencies to implement STEAM learning. This is due to the lack of knowledge and understanding of teachers about STEAM. This research is expected to contribute to the novelty of teachers’ readiness and beliefs in STEAM education in the city of Bandung